Activation of TRPV1 by capsaicin-loaded CaCO3 nanoparticle for tumor-specific therapy. (May 2022) - Xu, Mengqing; Zhang, Jin; Mu, Yongli; Foda, Mohamed Frahat; Han, Heyou
Abstract: Capsaicin is a natural non-toxic small molecular organic substance, which is often used clinically to reduce inflammation and pain. Here, we report an acid-responsive CaCO3 nanoparticle loaded with capsaicin that can specifically activate TRPV1 channels and trigger tumor calcium ion therapy. The excellent acid responsiveness of calcium carbonate enables it to precisely target the tumor sites. The released capsaicin can specifically activate TRPV1 channel, overloading the intracellular calcium ion concentration and causing cell apoptosis, which provides a new safer and cheaper treatment. We proved that the naturalness and non-toxicity of capsaicin make the CaCO3 @CAP nanoparticles have excellent biocompatibility, which has good development prospects and clinical application potential.